Catalyst protective agent with synergistic effect as well as preparation method and application of catalyst protective agent
By developing a catalyst protector based on specific composition and preparation methods to form a honeycomb structure, the problems of high cost, short life and single action of existing catalyst protectors are solved, and the effects of extending the catalyst life, improving purification efficiency and expanding the application range are achieved.
Patent Information
- Application Number
- CN202311278133.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-28
- Publication Date
- 2025-04-04
AI Technical Summary
The existing catalyst protectors are expensive, have short service life, are easy to leak and have a single effect, and cannot form synergistic effects with the catalyst, which limits their application in exhaust gas treatment.
A catalyst protector based on silica, aluminum trioxide, metal oxide, etc. is developed to form a honeycomb structure through a specific preparation method to enhance its strength, specific surface area and pore volume, thereby acting synergistically with the catalyst.
It extends the life of the catalyst, improves the purification efficiency, expands the application range of the catalyst, and solves the problems of high cost, short life and single action of existing catalyst protectors.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The invention relates to a catalyst protective agent with synergistic effect, a preparation method of the catalyst protective agent and application of the catalyst protective agent in tail gas treatment. Prior art
[0002] With the increasing national environmental protection requirements, the requirement of building green enterprises in an all-round way is imminent. The treatment of volatile organic compounds (VOCs) is closely related to the survival and development of enterprises. Catalytic oxidation is one of the most effective methods for treating waste gas containing VOCs. The main principle of this method is that under the action of a catalyst, harmful VOCs react with oxygen at low temperature to generate CO2 and H2O. The catalyst is the core of this treatment technology. However, the catalyst is easily deactivated or contaminated during the reaction, resulting in a decrease in catalyst efficiency, thereby affecting the treatment effect of the waste gas. Especially when treating sulfide-containing waste gas, the sulfur in the sulfide is very easy to combine with the active center of the catalyst, occupying the active center of the catalyst in the form of stable sulfur-containing salts, causing the catalyst to be poisoned and lose its catalytic activity. Therefore, a catalyst protector is needed to protect the catalyst and improve its stability and activity.
[0003] CN201910784042.1 relates to a sulfur-resistant shift catalyst protective agent and a preparation method thereof. The active components of the protective agent are ternary components of tungsten, nickel and iron, and waste iron oxide desulfurizer is used as the main raw material.
[0004] CN200910038286.1 discloses a catalyst protective agent, which mainly comprises the following components in percentage: 90-98.2% of carrier component Al2O3+SiO2; 0.8-1.2% of active component NiO; 1.0-1.5% of active component MoO3.
[0005] CN202010895379.2 relates to a sulfur-resistant shift catalyst protective agent and a preparation method thereof. The sulfur-resistant shift catalyst protective agent is prepared by a kneading method using acid-TiO2-modified sepiolite as a carrier, copper and cobalt as active components.
[0006] CN201811039085.9 relates to a methanol synthesis catalyst protective agent and a preparation method thereof. The catalyst has multiple metal active centers, one of which is a traditional Cu-based active center, and the other is M (M = one or two of Pb, Os, Ir, Pt, Ru, Rh, Pd). The multiple metal active centers act synergistically to obtain a methanol synthesis catalyst protective agent with better activity.
[0007] Currently, most of the catalyst protectors reported in existing technology and on the market are in granular or powder form, some of which are prepared using precious metals, and some of which have complicated preparation processes. Moreover, these catalyst protectors only have a desulfurization effect and cannot form a synergistic effect with the catalyst, resulting in these catalyst protectors being expensive, short in service life, easy to leak, and having a single function, which greatly limits the catalyst protectors in practical applications.
[0008] Therefore, it is necessary to develop a catalyst protector that is better, cheaper, more stable, and has a synergistic effect with the catalyst to further improve the application effect of the catalyst protector. Summary of the invention
[0009] The purpose of the present invention is to provide a catalyst protective agent and a preparation method of the catalyst protective agent and the application of the catalyst protective agent in tail gas treatment. The catalyst protective agent is a catalyst protective agent of better quality, cheaper and better stability and can work synergistically with the catalyst to achieve the effect of extending the life of the catalyst, improving the purification efficiency and expanding the application range of the catalyst, thereby solving the problems of the catalyst protective agent in the prior art, such as high price, short service life, easy leakage and single function.
[0010] The first aspect of the present invention is to provide a catalyst protective agent, which comprises the following components in weight percentage based on the catalyst protective agent:
[0011] Silicon dioxide 30-50%,
[0012] Aluminum oxide 30-50%,
[0013] Magnesium dioxide 0-10%, and
[0014] 5-20% of metal oxide, wherein the metal oxide is selected from one or more of ZnO, SnO, CuO, MnO2, ZrO2, CeO2 and CoO, preferably one or more of CuO, MnO2, ZrO2 and CeO2.
[0015] The content of the silicon dioxide is, for example, 35% by weight or 40% by weight.
[0016] The content of the aluminum oxide is, for example, 35 wt % or 40 wt %.
[0017] The content of the magnesium dioxide is, for example, 5% by weight.
[0018] The content of the metal oxide is, for example, 10 wt % or 15 wt %.
[0019] The strength of the catalyst protective agent is preferably 241-265 N / cm, for example 241, 242, 243, 245, 255, 256, 258, 259, 260, 261, 262, 263, 264, 265 N / cm; the specific surface area is preferably 204-242 m 2 / g, for example, 204, 209, 215, 238, 239, 240, 241, 242m 2 / g; and / or the pore volume is preferably 0.33 to 0.43 cm 3 / g, for example, 0.33, 0.34, 0.35, 0.38, 0.41, 0.42, 0.43 cm 3 / g. The strength of the catalyst protective agent is determined according to GB / T 1482-2010 "Test method for crushing strength and wear resistance of granular materials", and the specific surface area and pore volume are determined according to GB-T19587-2004 "Gas adsorption BET method for determination of specific surface area of solid substances".
[0020] The second aspect of the present invention is to provide a method for preparing a catalyst protective agent, which comprises the following preparation steps:
[0021] 1) mixing a carrier component containing Si, Al and optionally Mg, a lubricant, a foaming agent, a binder, a metal oxide and water in a certain weight ratio to obtain a mixture, and kneading the mixture in a kneader for a certain time;
[0022] 2) adding the mixture after the kneading treatment in step 1) into a vacuum clay kneading machine and repeatedly kneading until a plasticine-like clay material is formed;
[0023] 3) ageing the plasticine-like clay obtained in step 2) at 0 to 50° C., preferably at room temperature, in an airtight state for a certain period of time;
[0024] 4) using an extruder with a honeycomb mold to extrude the aged clay material in step 3) to obtain a honeycomb green body;
[0025] 5) drying the honeycomb green body in step 4) at room temperature for a certain period of time, and then drying it at an elevated temperature for a period of time to obtain a dry honeycomb material;
[0026] 6) The dried honeycomb material in step 5) is calcined at a certain temperature for a certain time to obtain a catalyst protective agent.
[0027] In one embodiment, the carrier component containing Si, Al and optionally Mg is selected from attapulgite clay, zeolite powder and clay, preferably attapulgite clay. The attapulgite clay is preferably in powder form, and its particle size range is preferably 0.1 to 100 μm, more preferably 0.5 to 20 μm. The content of the carrier component containing Si, Al and optionally Mg is preferably 10 to 50% by weight, more preferably 25 to 35% by weight based on the mixture.
[0028] In one embodiment, the lubricant is selected from glycerol, vaseline and olive oil, etc., preferably glycerol. The content of the lubricant is preferably 1-15% by weight, more preferably 3-5% by weight, based on the mixture.
[0029] In one embodiment, the foaming agent is selected from glucose, sodium bicarbonate and calcium hydroxide, preferably glucose. The content of the foaming agent is preferably 1 to 10 weight %, more preferably 2 to 4 weight %, based on the mixture.
[0030] In one embodiment, the binder is selected from one or more of silica sol, aluminum sol, starch, hydroxymethyl cellulose and polyvinyl alcohol, preferably one or more of silica sol, aluminum sol and hydroxymethyl cellulose. The content of the binder is preferably 5 to 30% by weight, more preferably 5 to 10% by weight based on the mixture.
[0031] In one embodiment, the metal oxide is selected from one or more of ZnO, SnO, CuO, MnO2, ZrO2, CeO2 and CoO, preferably one or more of CuO, MnO2, ZrO2 and CeO2. The content of the metal oxide is preferably 1 to 20% by weight, more preferably 5 to 10% by weight based on the mixture.
[0032] In one embodiment, the water is deionized water. The content of the water is preferably 30 to 70% by weight, more preferably 40 to 60% by weight, based on the mixture.
[0033] In one embodiment, the kneading treatment time in step 1) is 0.5 to 24 hours, preferably 2 to 6 hours.
[0034] In one embodiment, the number of repeated mud kneading in step 2) is 2 to 15 times, preferably 5 to 10 times.
[0035] In one embodiment, the aging time in step 3) is 1 to 48 hours, more preferably 6 to 12 hours.
[0036] In one embodiment, the extruder with a honeycomb die is a hydraulic vertical extruder with a honeycomb die.
[0037] In one embodiment, the extrusion pressure in step 4) is 0.5-20 MPa, more preferably 2-5 MPa.
[0038] In one embodiment, in step 5), the honeycomb green body is dried at room temperature for 1 to 48 hours, preferably 12 to 24 hours. Drying at room temperature here refers to air drying in a room temperature drying environment, for example.
[0039] In one embodiment, in step 5), the drying under elevated temperature conditions refers to drying at 60-200° C., preferably 80-120° C., for 1-24 hours, preferably 2-6 hours.
[0040] In one embodiment, in step 6), the calcination refers to calcination at 400-800° C., preferably 500-600° C., for 2-24 hours, more preferably 4-6 hours.
[0041] The third aspect of the present invention is the use of the catalyst protective agent of the present invention in waste gas treatment. The waste gas, for example, refers to waste gas containing sulfide. The waste gas treatment, for example, refers to tail gas treatment.
[0042] The catalyst protector obtained by the present invention is of higher quality, lower price and better stability than the catalyst protectors in the prior art, and can produce a synergistic effect when used together with a catalyst, thereby extending the life of the catalyst, improving the purification efficiency and expanding the application range of the catalyst, thereby solving the problems of the catalyst protectors in the prior art, such as high price, short service life, easy leakage and single function. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Attached Figure 1 Flow chart of the performance testing device of the catalyst protective agent of the present invention
[0044] Attached Figure 2 This is a comparison chart of the protective performance of protective agents 1-16, 2-1 and 2-2
[0045] Attached Figure 3 This is a comparison chart of the protective performance of protective agents 1-17, 2-1, and 2-2
[0046] Attached Figure 4 This is a comparison chart of the protective performance of protective agents 1-18, 2-1, and 2-2 DETAILED DESCRIPTION
[0047] The embodiments of the present invention will be described in detail below with reference to examples, but those skilled in the art will appreciate that the following examples are only used to illustrate the present invention and should not be construed as limiting the scope of the present invention.
[0048] Example
[0049] The present invention is further described in detail below using examples, but the present invention is not limited to these examples.
[0050] Example 1
[0051] 1. 30 g (30 wt%) of powdered zeolite powder (particle size range: 2-10 μm), 3 g (3 wt%) of vaseline, 2 g (2 wt%) of glucose, 10 g (10 wt%) of aluminum sol, 3.5 g (3.5 wt%) of CuO, 3.5 g (3.5 wt%) of MnO2, 3 g (3 wt%) of CeO2, and 45 g (45 wt%) of deionized water were mixed and kneaded in a kneader for 6 hours;
[0052] 2. Then add the mixed material into the vacuum mud kneading machine and repeat the mud kneading 8 times to form a plasticine-like mud material;
[0053] 3. The prepared clay is sealed and aged at room temperature for 12 hours in an airtight manner;
[0054] 4. Use a hydraulic vertical extruder with a honeycomb mold to extrude the aged mud material at an extrusion pressure of 5 MPa to obtain a honeycomb green body;
[0055] 5. Dry at room temperature for 24 hours and at 120°C for 6 hours;
[0056] 6. The dried honeycomb material was calcined at 500°C for 6 hours to obtain an integral honeycomb catalyst protective agent, No. 1-1.
[0057] Its composition is: silicon dioxide (40 weight%), aluminum oxide (30 weight%), magnesium dioxide (10 weight%), CuO (7 weight%), MnO2 (7 weight%), and CeO2 (6 weight%).
[0058] Its strength is 243N / m, specific surface area is 215㎡ / g, and pore volume is 0.33cm 3 / g.
[0059] Example 2
[0060] 1. 30 g (30 wt%) of powdered clay (particle size range: 2-10 μm), 3 g (3 wt%) of olive oil, 2 g (2 wt%) of sodium bicarbonate, 10 g (10 wt%) of aluminum sol, 3.5 g (3.5 wt%) of CuO, 3.5 g (3.5 wt%) of MnO2, 3 g (3 wt%) of CeO2, and 45 g (45 wt%) of deionized water were mixed and kneaded in a kneader for 6 hours;
[0061] 2. Then add the mixed material into the vacuum mud kneading machine and repeat the mud kneading 8 times to form a plasticine-like mud material;
[0062] 3. The prepared clay is sealed and aged at room temperature for 12 hours in an airtight manner;
[0063] 4. Use a hydraulic vertical extruder with a honeycomb mold to extrude the aged mud material at an extrusion pressure of 5 MPa to obtain a honeycomb green body;
[0064] 5. Dry at room temperature for 24 hours and at 120°C for 6 hours;
[0065] 6. The dried honeycomb material was calcined at 500°C for 6 hours to obtain an integral honeycomb catalyst protective agent, No. 1-2.
[0066] Its composition is: silicon dioxide (40 weight%), aluminum oxide (40 weight%), CuO (7 weight%), MnO2 (7 weight%), and CeO2 (6 weight%).
[0067] Its strength is 242N / m, specific surface area is 209㎡ / g, and pore volume is 0.34cm 3 / g.
[0068] Example 3
[0069] 1. 30 g (30 wt%) of powdered clay (particle size range: 2-10 μm), 3 g (3 wt%) of olive oil, 2 g (2 wt%) of calcium hydroxide, 10 g (10 wt%) of aluminum sol, 3.5 g (3.5 wt%) of ZnO, 3.5 g (3.5 wt%) of MnO2, 3 g (3 wt%) of CeO2, and 45 g (45 wt%) of deionized water were mixed and kneaded in a kneader for 6 hours;
[0070] 2. Then add the mixed material into the vacuum mud kneading machine and repeat the mud kneading 8 times to form a plasticine-like mud material;
[0071] 3. The prepared clay is sealed and aged at room temperature for 12 hours in an airtight manner;
[0072] 4. Use a hydraulic vertical extruder with a honeycomb mold to extrude the aged mud material at an extrusion pressure of 5 MPa to obtain a honeycomb green body;
[0073] 5. Dry at room temperature for 24 hours and at 120°C for 6 hours;
[0074] 6. The dried honeycomb material was calcined at 500°C for 6 hours to obtain an integral honeycomb catalyst protective agent, numbered 1-3.
[0075] Its composition is: silicon dioxide (40 weight%), aluminum oxide (40 weight%), ZnO (7 weight%), MnO2 (7 weight%), and CeO2 (6 weight%).
[0076] Its strength is 245N / m, specific surface area is 204㎡ / g, and pore volume is 0.35cm 3 / g.
[0077] Example 4
[0078] 1. 30 g (30 wt%) of powdered attapulgite clay (particle size range: 2-10 μm), 3 g (3 wt%) of olive oil, 2 g (2 wt%) of sodium bicarbonate, 10 g (10 wt%) of aluminum sol, 3.5 g (3.5 wt%) of ZnO, 3.5 g (3.5 wt%) of CuO, 3 g (3 wt%) of CeO2, and 45 g (45 wt%) of deionized water were mixed and kneaded in a kneader for 6 hours;
[0079] 2. Then add the mixed material into the vacuum mud kneading machine and repeat the mud kneading 8 times to form a plasticine-like mud material;
[0080] 3. The prepared clay is sealed and aged at room temperature for 12 hours in an airtight manner;
[0081] 4. Use a hydraulic vertical extruder with a honeycomb mold to extrude the aged mud material at an extrusion pressure of 5 MPa to obtain a honeycomb green body;
[0082] 5. Dry at room temperature for 24 hours and at 120°C for 6 hours;
[0083] 6. The dried honeycomb material was calcined at 500°C for 6 hours to obtain an integral honeycomb catalyst protective agent, numbered 1-4.
[0084] Its composition is: silicon dioxide (35 weight%), aluminum oxide (40 weight%), magnesium dioxide (5 weight%), CuO (7 weight%), MnO2 (7 weight%), and CeO2 (6 weight%).
[0085] Its strength is 242N / m, specific surface area is 238㎡ / g, and pore volume is 0.42cm 3 / g.
[0086] Example 5
[0087] 1. 30 g (30 wt%) of powdered attapulgite clay (particle size range: 2-10 μm), 3 g (3 wt%) of vaseline, 2 g (2 wt%) of calcium hydroxide, 10 g (10 wt%) of aluminum sol, 3.5 g (3.5 wt%) of CuO, 3.5 g (3.5 wt%) of MnO2, 3 g (3 wt%) of CeO2, and 45 g (45 wt%) of deionized water were mixed and kneaded in a kneader for 6 hours;
[0088] 2. Then add the mixed material into the vacuum mud kneading machine and repeat the mud kneading 8 times to form a plasticine-like mud material;
[0089] 3. The prepared clay is sealed and aged at room temperature for 12 hours in an airtight manner;
[0090] 4. Use a hydraulic vertical extruder with a honeycomb mold to extrude the aged mud material at an extrusion pressure of 5 MPa to obtain a honeycomb green body;
[0091] 5. Dry at room temperature for 24 hours and at 120°C for 6 hours;
[0092] 6. The dried honeycomb material was calcined at 500°C for 6 hours to obtain an integral honeycomb catalyst protective agent, numbered 1-5.
[0093] Its composition is: silicon dioxide (35 weight%), aluminum oxide (40 weight%), magnesium dioxide (5 weight%), CuO (7 weight%), MnO2 (7 weight%), and CeO2 (6 weight%).
[0094] Its strength is 241N / m, specific surface area is 239㎡ / g, and pore volume is 0.42cm 3 / g.
[0095] Example 6
[0096] 1. 30 g (30 wt%) of powdered attapulgite clay (particle size range: 2-10 μm), 3 g (3 wt%) of glycerol, 2 g (2 wt%) of glucose, 10 g (10 wt%) of aluminum sol, 10 g (10 wt%) of CuO, and 45 g (45 wt%) of deionized water were mixed and kneaded in a kneader for 6 hours;
[0097] 2. Then add the mixed material into the vacuum mud kneading machine and repeat the mud kneading 8 times to form a plasticine-like mud material;
[0098] 3. The prepared clay is sealed and aged at room temperature for 12 hours in an airtight manner;
[0099] 4. Use a hydraulic vertical extruder with a honeycomb mold to extrude the aged mud material at an extrusion pressure of 5 MPa to obtain a honeycomb green body;
[0100] 5. Dry at room temperature for 24 hours and at 120°C for 6 hours;
[0101] 6. The dried honeycomb material was calcined at 500°C for 6 hours to obtain an integral honeycomb catalyst protective agent, numbered 1-6.
[0102] Its composition is: silicon dioxide (35 weight %), aluminum oxide (40 weight %), magnesium dioxide (5 weight %), and CuO (20 weight %).
[0103] Its strength is 265N / m, specific surface area is 241㎡ / g, and pore volume is 0.38cm 3 / g.
[0104] Example 7
[0105] 1. 30 g (30 wt%) of powdered attapulgite clay (particle size range: 2-10 μm), 3 g (3 wt%) of glycerol, 2 g (2 wt%) of glucose, 10 g (10 wt%) of aluminum sol, 10 g (10 wt%) of MnO2, and 45 g (45 wt%) of deionized water were mixed and kneaded in a kneader for 6 hours;
[0106] 2. Then add the mixed material into the vacuum mud kneading machine and repeat the mud kneading 8 times to form a plasticine-like mud material;
[0107] 3. The prepared clay is sealed and aged at room temperature for 12 hours in an airtight manner;
[0108] 4. Use a hydraulic vertical extruder with a honeycomb mold to extrude the aged mud material at an extrusion pressure of 5 MPa to obtain a honeycomb green body;
[0109] 5. Dry at room temperature for 24 hours and at 120°C for 6 hours;
[0110] 6. The dried honeycomb material was calcined at 500°C for 6 hours to obtain an integral honeycomb catalyst protective agent, numbered 1-7.
[0111] Its composition is: silicon dioxide (35 weight %), aluminum oxide (40 weight %), magnesium dioxide (5 weight %), and MnO2 (20 weight %).
[0112] Its strength is 255N / m, specific surface area is 239㎡ / g, and pore volume is 0.43cm 3 / g.
[0113] Example 8
[0114] 1. 30 g (30 wt%) of powdered attapulgite clay (particle size range of 2 to 10 μm), 3 g (3 wt%) of glycerol, 2 g (2 wt%) of glucose, 10 g (10 wt%) of aluminum sol, 10 g (10 wt%) of ZrO2, and 45 g (45 wt%) of deionized water were mixed and kneaded in a kneader for 6 hours;
[0115] 2. Then add the mixed material into the vacuum mud kneading machine and repeat the mud kneading 8 times to form a plasticine-like mud material;
[0116] 3. The prepared clay is sealed and aged at room temperature for 12 hours in an airtight manner;
[0117] 4. Use a hydraulic vertical extruder with a honeycomb mold to extrude the aged mud material at an extrusion pressure of 5 MPa to obtain a honeycomb green body;
[0118] 5. Dry at room temperature for 24 hours and at 120°C for 6 hours;
[0119] 6. The dried honeycomb material was calcined at 500°C for 6 hours to obtain an integral honeycomb catalyst protective agent, numbered 1-8.
[0120] Its composition is: silicon dioxide (35 weight %), aluminum oxide (40 weight %), magnesium dioxide (5 weight %), and ZrO2 (20 weight %).
[0121] Its strength is 263N / m, specific surface area is 241㎡ / g, and pore volume is 0.41cm 3 / g.
[0122] Example 9
[0123] 1. 30 g (30 wt%) of powdered attapulgite clay (particle size range: 2-10 μm), 3 g (3 wt%) of glycerol, 2 g (2 wt%) of glucose, 10 g (10 wt%) of aluminum sol, 10 g (10 wt%) of CeO2, and 45 g (45 wt%) of deionized water were mixed and kneaded in a kneader for 6 hours;
[0124] 2. Then add the mixed material into the vacuum mud kneading machine and repeat the mud kneading 8 times to form a plasticine-like mud material;
[0125] 3. The prepared clay is sealed and aged at room temperature for 12 hours in an airtight manner;
[0126] 4. Use a hydraulic vertical extruder with a honeycomb mold to extrude the aged mud material at an extrusion pressure of 5 MPa to obtain a honeycomb green body;
[0127] 5. Dry at room temperature for 24 hours and at 120°C for 6 hours;
[0128] 6. The dried honeycomb material was calcined at 500°C for 6 hours to obtain an integral honeycomb catalyst protective agent, numbered 1-9.
[0129] Its composition is: silicon dioxide (35 weight %), aluminum oxide (40 weight %), magnesium dioxide (5 weight %), and CeO2 (20 weight %).
[0130] Its strength is 260N / m, specific surface area is 242㎡ / g, and pore volume is 0.42cm 3 / g.
[0131] Example 10
[0132] 1. 30 g (30 wt%) of powdered attapulgite clay (particle size range: 2-10 μm), 3 g (3 wt%) of glycerol, 2 g (2 wt%) of glucose, 10 g (10 wt%) of aluminum sol, 10 g (10 wt%) of SnO, and 45 g (45 wt%) of deionized water were mixed and kneaded in a kneader for 6 hours;
[0133] 2. Then add the mixed material into the vacuum mud kneading machine and repeat the mud kneading 8 times to form a plasticine-like mud material;
[0134] 3. The prepared clay is sealed and aged at room temperature for 12 hours in an airtight manner;
[0135] 4. Use a hydraulic vertical extruder with a honeycomb mold to extrude the aged mud material at an extrusion pressure of 5 MPa to obtain a honeycomb green body;
[0136] 5. Dry at room temperature for 24 hours and at 120°C for 6 hours;
[0137] 6. The dried honeycomb material was calcined at 500°C for 6 hours to obtain an integral honeycomb catalyst protective agent, numbered 1-10.
[0138] Its composition is: silicon dioxide (35 weight %), aluminum oxide (40 weight %), magnesium dioxide (5 weight %), and SnO (20 weight %).
[0139] Its strength is 263N / m, specific surface area is 238㎡ / g, and pore volume is 0.42cm 3 / g.
[0140] Embodiment 11
[0141] 1. 30 g (30 wt%) of powdered attapulgite clay (particle size range: 2-10 μm), 3 g (3 wt%) of glycerol, 2 g (2 wt%) of glucose, 10 g (10 wt%) of aluminum sol, 10 g (10 wt%) of CoO, and 45 g (45 wt%) of deionized water were mixed and kneaded in a kneader for 6 hours;
[0142] 2. Then add the mixed material into the vacuum mud kneading machine and repeat the mud kneading 8 times to form a plasticine-like mud material;
[0143] 3. The prepared clay is sealed and aged at room temperature for 12 hours in an airtight manner;
[0144] 4. Use a hydraulic vertical extruder with a honeycomb mold to extrude the aged mud material at an extrusion pressure of 5 MPa to obtain a honeycomb green body;
[0145] 5. Dry at room temperature for 24 hours and at 120°C for 6 hours;
[0146] 6. The dried honeycomb material was calcined at 500°C for 6 hours to obtain an integral honeycomb catalyst protective agent, numbered 1-11.
[0147] Its composition is: silicon dioxide (35 weight %), aluminum oxide (40 weight %), magnesium dioxide (5 weight %), and CoO (20 weight %).
[0148] Its strength is 258N / m, specific surface area is 239㎡ / g, and pore volume is 0.42cm 3 / g.
[0149] Example 12
[0150] 1. 30 g (30 wt%) of powdered attapulgite clay (particle size range: 2-10 μm), 3 g (3 wt%) of glycerol, 2 g (2 wt%) of glucose, 10 g (10 wt%) of aluminum sol, 5 g (5 wt%) of CuO, 5 g (5 wt%) of CeO2 and 45 g (45 wt%) of deionized water were mixed and kneaded in a kneader for 6 hours;
[0151] 2. Then add the mixed material into the vacuum mud kneading machine and repeat the mud kneading 8 times to form a plasticine-like mud material;
[0152] 3. The prepared clay is sealed and aged at room temperature for 12 hours in an airtight manner;
[0153] 4. Use a hydraulic vertical extruder with a honeycomb mold to extrude the aged mud material at an extrusion pressure of 5 MPa to obtain a honeycomb green body;
[0154] 5. Dry at room temperature for 24 hours and at 120°C for 6 hours;
[0155] 6. The dried honeycomb material was calcined at 500°C for 6 hours to obtain an integral honeycomb catalyst protective agent, numbered 1-12.
[0156] Its composition is: silicon dioxide (35 weight%), aluminum oxide (40 weight%), magnesium dioxide (5 weight%), CuO (10 weight%), and CeO2 (10 weight%).
[0157] Its strength is 256N / m, specific surface area is 242㎡ / g, and pore volume is 0.41cm 3 / g.
[0158] Embodiment 13
[0159] 1. 30 g (30 wt%) of powdered attapulgite clay (particle size range of 2 to 10 μm), 3 g (3 wt%) of glycerol, 2 g (2 wt%) of glucose, 10 g (10 wt%) of aluminum sol, 5 g (5 wt%) of MnO2, 5 g (5 wt%) of CeO2, and 45 g (45 wt%) of deionized water were mixed and kneaded in a kneader for 6 hours;
[0160] 2. Then add the mixed material into the vacuum mud kneading machine and repeat the mud kneading 8 times to form a plasticine-like mud material;
[0161] 3. The prepared clay is sealed and aged at room temperature for 12 hours in an airtight manner;
[0162] 4. Use a hydraulic vertical extruder with a honeycomb mold to extrude the aged mud material at an extrusion pressure of 5 MPa to obtain a honeycomb green body;
[0163] 5. Dry at room temperature for 24 hours and at 120°C for 6 hours;
[0164] 6. The dried honeycomb material was calcined at 500°C for 6 hours to obtain an integral honeycomb catalyst protective agent, numbered 1-13.
[0165] Its composition is: silicon dioxide (35 weight%), aluminum oxide (40 weight%), magnesium dioxide (5 weight%), MnO2 (10 weight%), and CeO2 (10 weight%).
[0166] Its strength is 260N / m, specific surface area is 241㎡ / g, and pore volume is 0.40cm 3 / g.
[0167] Embodiment 14
[0168] 1. 30 g (30 wt%) of powdered attapulgite clay (particle size range: 2-10 μm), 3 g (3 wt%) of glycerol, 2 g (2 wt%) of glucose, 10 g (10 wt%) of aluminum sol, 5 g (5 wt%) of CuO, 5 g (5 wt%) of ZrO2, and 45 g (45 wt%) of deionized water were mixed and kneaded in a kneader for 6 hours;
[0169] 2. Then add the mixed material into the vacuum mud kneading machine and repeat the mud kneading 8 times to form a plasticine-like mud material;
[0170] 3. The prepared clay is sealed and aged at room temperature for 12 hours in an airtight manner;
[0171] 4. Use a hydraulic vertical extruder with a honeycomb mold to extrude the aged mud material at an extrusion pressure of 5 MPa to obtain a honeycomb green body;
[0172] 5. Dry at room temperature for 24 hours and at 120°C for 6 hours;
[0173] 6. The dried honeycomb material was calcined at 500°C for 6 hours to obtain an integral honeycomb catalyst protective agent, numbered 1-14.
[0174] Its composition is: silicon dioxide (35 weight%), aluminum oxide (40 weight%), magnesium dioxide (5 weight%), CuO (10 weight%), and ZrO2 (10 weight%).
[0175] Its strength is 258N / m, specific surface area is 242㎡ / g, and pore volume is 0.42cm 3 / g.
[0176] Embodiment 15
[0177] 1. 30 g (30 wt%) of powdered attapulgite clay (particle size range: 2-10 μm), 3 g (3 wt%) of glycerol, 2 g (2 wt%) of glucose, 10 g (10 wt%) of aluminum sol, 5 g (5 wt%) of MnO2, 5 g (5 wt%) of ZrO2, and 45 g (45 wt%) of deionized water were mixed and kneaded in a kneader for 6 hours;
[0178] 2. Then add the mixed material into the vacuum mud kneading machine and repeat the mud kneading 8 times to form a plasticine-like mud material;
[0179] 3. The prepared clay is sealed and aged at room temperature for 12 hours in an airtight manner;
[0180] 4. Use a hydraulic vertical extruder with a honeycomb mold to extrude the aged mud material at an extrusion pressure of 5 MPa to obtain a honeycomb green body;
[0181] 5. Dry at room temperature for 24 hours and at 120°C for 6 hours;
[0182] 6. The dried honeycomb material was calcined at 500°C for 6 hours to obtain an integral honeycomb catalyst protective agent, numbered 1-15.
[0183] Its composition is: silicon dioxide (35 weight%), aluminum oxide (40 weight%), magnesium dioxide (5 weight%), MnO2 (10 weight%), and ZrO2 (10 weight%).
[0184] Its strength is 264N / m, specific surface area is 242㎡ / g, and pore volume is 0.43cm 3 / g.
[0185] Example 16
[0186] 1. 30 g (30 wt%) of powdered attapulgite clay (particle size range: 2-10 μm), 3 g (3 wt%) of glycerol, 2 g (2 wt%) of glucose, 10 g (10 wt%) of aluminum sol, 3.5 g (3.5 wt%) of CuO, 3.5 g (3.5 wt%) of MnO2, 3 g (3 wt%) of CeO2, and 45 g (45 wt%) of deionized water were mixed and kneaded in a kneader for 6 hours;
[0187] 2. Then add the mixed material into the vacuum mud kneading machine and repeat the mud kneading 8 times to form a plasticine-like mud material;
[0188] 3. The prepared clay is sealed and aged at room temperature for 12 hours in an airtight manner;
[0189] 4. Use a hydraulic vertical extruder with a honeycomb mold to extrude the aged mud material at an extrusion pressure of 5 MPa to obtain a honeycomb green body;
[0190] 5. Dry at room temperature for 24 hours and at 120°C for 6 hours;
[0191] 6. The dried honeycomb material was calcined at 500°C for 6 hours to obtain an integral honeycomb catalyst protective agent, numbered 1-16.
[0192] Its composition is: silicon dioxide (35 weight%), aluminum oxide (40 weight%), magnesium dioxide (5 weight%), CuO (10 weight%), and MnO2 (10 weight%).
[0193] Its strength is 262N / m, specific surface area is 240㎡ / g, and pore volume is 0.42cm 3 / g.
[0194] Embodiment 17
[0195] 1. 30 g (30 wt%) of powdered attapulgite clay (particle size range: 2-10 μm), 3 g (3 wt%) of glycerol, 2 g (2 wt%) of glucose, 10 g (10 wt%) of aluminum sol, 3.5 g (3.5 wt%) of CuO, 3.5 g (3.5 wt%) of MnO2, 3 g (3 wt%) of ZrO2, and 45 g (45 wt%) of deionized water were mixed and kneaded in a kneader for 6 hours;
[0196] 2. Then add the mixed material into the vacuum mud kneading machine and repeat the mud kneading 8 times to form a plasticine-like mud material;
[0197] 3. The prepared clay is sealed and aged at room temperature for 12 hours in an airtight manner;
[0198] 4. Use a hydraulic vertical extruder with a honeycomb mold to extrude the aged mud material at an extrusion pressure of 5 MPa to obtain a honeycomb green body;
[0199] 5. Dry at room temperature for 24 hours and at 120°C for 6 hours;
[0200] 6. The dried honeycomb material was calcined at 500°C for 6 hours to obtain an integral honeycomb catalyst protective agent, numbered 1-17.
[0201] Its composition is: silicon dioxide (35 weight%), aluminum oxide (40 weight%), magnesium dioxide (5 weight%), CuO (7 weight%), MnO2 (7 weight%), and ZrO (6 weight%)2.
[0202] Its strength is 259N / m, specific surface area is 239㎡ / g, and pore volume is 0.41cm 3 / g.
[0203] Embodiment 18
[0204] 1. 30 g (30 wt%) of powdered attapulgite clay (particle size range: 2-10 μm), 3 g (3 wt%) of glycerol, 2 g (2 wt%) of glucose, 10 g (10 wt%) of aluminum sol, 2.5 g (2.5 wt%) of CuO, 2.5 g (2.5 wt%) of MnO2, 2.5 g (2.5 wt%) of ZrO2, 2.5 g (2.5 wt%) of CeO2, and 45 g (45 wt%) of deionized water were mixed and kneaded in a kneader for 6 hours;
[0205] 2. Then add the mixed material into the vacuum mud kneading machine and repeat the mud kneading 8 times to form a plasticine-like mud material;
[0206] 3. The prepared clay is sealed and aged at room temperature for 12 hours in an airtight manner;
[0207] 4. Use a hydraulic vertical extruder with a honeycomb mold to extrude the aged mud material at an extrusion pressure of 5 MPa to obtain a honeycomb green body;
[0208] 5. Dry at room temperature for 24 hours and at 120°C for 6 hours;
[0209] 6. The dried honeycomb material was calcined at 500°C for 6 hours to obtain an integral honeycomb catalyst protective agent, numbered 1-18.
[0210] Its composition is: silicon dioxide (35 weight%), aluminum oxide (40 weight%), magnesium dioxide (5 weight%), CuO (5 weight%), MnO2 (5 weight%), ZrO (5 weight%), and CeO2 (5 weight%).
[0211] Its strength is 265N / m, specific surface area is 238㎡ / g, and pore volume is 0.43cm 3 / g.
[0212] Comparative Example
[0213] Comparative Example 1
[0214] The catalyst protective agent was prepared by the method in Example 5 of patent CN202010895379.2 for comparison of various performance indicators. The specific preparation method is as follows:
[0215] 1) dissolving 2.2 g of α-titanic acid in 70 mL of dilute nitric acid solution to prepare a modified solution; adding the modified solution to 86 g of sepiolite and kneading for 4 hours, standing for 10 hours, drying at 120° C. for 12 hours, calcining at 430° C. for 10 hours, and crushing to less than 160 mesh to obtain modified sepiolite;
[0216] 2) Weigh 9.4 g of copper nitrate and 7.9 g of cobalt nitrate, add to 50 mL of deionized water to obtain a clear solution A5. Add 6 g of citric acid and 6 mL of nitric acid to 20 mL of deionized water to obtain a solution B5;
[0217] 3) Weigh the modified sepiolite, add 1.8g of metatitanic acid powder and 6g of sesbania powder, mix evenly, add solution A5, knead evenly, then add solution B5, knead evenly, shape, dry naturally, and then calcine at 460°C for 8 hours to obtain a catalyst protective agent, No. 2-1.
[0218] Comparative Example 2
[0219] The method of Example 18 is adopted, but without adding metal oxide, and the specific preparation method is as follows:
[0220] 1. 30 g (30 wt%) of powdered attapulgite clay (particle size range: 2-10 μm), 3 g (3 wt%) of glycerol, 2 g (2 wt%) of glucose, 10 g (10 wt%) of aluminum sol, and 55 g (50 wt%) of deionized water were mixed and kneaded in a kneader for 6 hours;
[0221] 2. Then add the mixed material into the vacuum mud kneading machine and repeat the mud kneading 8 times to form a plasticine-like mud material;
[0222] 3. The prepared clay is sealed and aged at room temperature for 12 hours in an airtight manner;
[0223] 4. Use a hydraulic vertical extruder with a honeycomb mold to extrude the aged mud material at an extrusion pressure of 5 MPa to obtain a honeycomb green body;
[0224] 5. Dry at room temperature for 24 hours and at 120°C for 6 hours;
[0225] 6. The dried honeycomb material was calcined at 500°C for 6 hours to obtain an integral honeycomb catalyst protective agent, No. 2-2.
[0226] Evaluation and comparison test
[0227] The catalyst protective agent prepared by the method of the present invention is a shaped honeycomb product, which can be made into various honeycomb shapes as required, and has the advantages of not being easy to wear, being conducive to gas distribution, and uniform flow guidance during use. Since the protective agent for comparative evaluation is in powder form, in order to reflect the accuracy of the comparison, we crushed the protective agent of the entire honeycomb and screened the powder below 160 mesh for evaluation. It should be noted that crushing itself will reduce the strength performance of some protective agents.
[0228] (I) Basic performance test
[0229] The water boiling treatment strengthening test was adopted to examine the basic properties of the protective agent before and after normal pressure water boiling treatment, including strength, specific surface area and pore volume. The results are shown in Table 1.
[0230] Boiling test conditions: Take a certain amount of protective agent and boil it in boiling water for 3 hours. After drying, measure the changes in the strength, specific surface and pore volume of the protective agent. The strength is measured using GB / T 1482-2010 "Test method for crushing strength and wear resistance of granular materials", and the specific surface and pore volume are measured using GB-T19587-2004 "Gas adsorption BET method for determination of specific surface area of solid substances".
[0231] Table 1 Comparison of protective agent strength, specific surface area, pore volume and hydrothermal stability
[0232]
[0233]
[0234] (II) Protection performance test
[0235] In the attached Figure 1 In the test process shown, the protective performance of protective agents 1-16, 1-17, 1-18, 2-1, and 2-2 on the catalyst was tested. The catalyst used in the test was the YPVC-400 tail gas catalyst of Yangzi Petrochemical.
[0236] Protection performance test conditions: Figure 1 In the test process shown, the configuration contains 1000mg / Nm 3 Air containing toluene and configuration containing 1000mg / Nm 3 The air containing SO2 is respectively loaded into steel cylinders, and the protective agent and catalyst to be tested are loaded into the reactor (the airflow direction is from top to bottom, the catalyst is loaded at the bottom, and the protective agent is loaded at the top, and the loading amount is 10ml). First, the air containing toluene is introduced (the flow rate of FI-101 is controlled to be 100L / h), and the temperature is raised from the initial temperature of 150℃ (TT-101 temperature), and the toluene concentration at the outlet is detected. When the chromatogram detects that the toluene content in the gas drops to ≤10mg / Nm 3 , that is, reaching T 99 When the temperature is raised, the temperature of TT-101 is kept constant. Then, air containing SO2 is introduced, and the flow rate of FI-102 is controlled to be 10L / h, and the flow rate of FI-101 is controlled to be 90L / h, that is, the SO2 concentration is 100mg / Nm 3 , the toluene conversion rate was detected with constant flow and temperature over time. The results are shown in Figures 2 to 4 .
[0237] (III) Collaborative performance test
[0238] In the attached Figure 1 In the test process shown, the synergistic performance of each protective agent and catalyst was tested, and the catalyst used in the test was the YPVC-400 tail gas catalyst of Yangzi Petrochemical.
[0239] Synergy performance test conditions: as shown in the attached Figure 1 In the test process shown (air containing SO2 is not used here), the configuration contains 1000mg / Nm 3 Toluene-containing air is put into a steel cylinder, and the protective agent and catalyst to be tested are filled in the reactor (the airflow direction is from top to bottom, the catalyst is filled in the bottom, and the protective agent is filled in the top, and the filling amount is 10ml). Toluene-containing air is introduced (the FI-101 flow rate is controlled at 100L / h), and the temperature is increased from the initial temperature of 150℃ (TT-101 temperature). The outlet toluene concentration is detected. When the chromatogram detects that the toluene content in the gas drops to ≤10mg / Nm 3 , that is, reaching T 99When the temperature reaches T, record the temperature and observe the 99 The lower the temperature, the better the synergistic effect with the catalyst and the stronger the synergistic performance. The results are shown in Table 3.
[0240] Table 3 Test results of protective agent synergistic performance
[0241] name <![CDATA[Toluene T 99 Temperature °C]]> <![CDATA[Toluene T 99 Temperature decrease °C]]> blank 265 0 1-1 247 18 1-2 249 16 1-3 252 13 1-4 251 14 1-5 248 17 1-6 242 23 1-7 243 22 1-8 252 13 1-9 253 12 1-10 254 11 1-11 253 12 1-12 249 16 1-13 248 17 1-14 246 19 1-15 243 22 1-16 246 19 1-17 247 18 1-18 241 24 2-1 258 7 2-2 265 0
Claims
1. A honeycomb catalyst protective agent, which comprises the following components in percentage by weight based on the catalyst protective agent: Silicon dioxide 30-50%, Aluminum oxide 30-50%, Magnesium dioxide 0-10%, and 5-20% of metal oxide, wherein the metal oxide is selected from one or more of ZnO, SnO, CuO, MnO2, ZrO2, CeO2 and CoO, preferably one or more of CuO, MnO2, ZrO2 and CeO2.
2. The honeycomb catalyst protective agent according to claim 1, wherein The strength of the protective agent is 241-265N / cm2, and the specific surface area is 204-242m2. 2 / g and / or pore volume of 0.33 to 0.43 cm 3 / g, and / or The protective agent is of integral honeycomb type.
3. The method for preparing the honeycomb catalyst protective agent according to any one of the above claims, comprising the following preparation steps: 1) mixing a carrier component containing Si, Al and optionally Mg, a lubricant, a foaming agent, a binder, a metal oxide and deionized water in a certain weight ratio to obtain a mixture, and kneading the mixture in a kneader for a certain time; 2) adding the mixture after the kneading treatment in step 1) into a vacuum clay kneading machine and repeatedly kneading until a plasticine-like clay material is formed; 3) The clay obtained in step 2) is sealed and aged for a period of time at 0-50° C., preferably at room temperature, isolated from air; 4) Extruding the aged clay material in step 3) by an extruder with a honeycomb mold, preferably a hydraulic vertical extruder with a honeycomb mold, to obtain a honeycomb embryo body; 5) drying the honeycomb green body in step 4) at room temperature for a certain period of time, and then drying it at an elevated temperature for a period of time to obtain a dry honeycomb material; 6) The honeycomb material dried in step 5) is calcined at a certain temperature for a certain time to obtain a honeycomb catalyst protective agent.
4. The preparation method according to claim 3, wherein the carrier component containing Si, Al and optionally Mg in step 1) is selected from attapulgite clay, zeolite powder and clay, preferably attapulgite clay; the attapulgite clay is preferably in powder form, and its particle size range is preferably 0.1 to 100 μm, more preferably 0.5 to 20 μm; and / or The content of the support component containing Si, Al and optionally Mg is 10 to 50% by weight, preferably 25 to 35% by weight, based on the mixture.
5. The preparation method according to claim 3 or 4, wherein the lubricant is selected from glycerol, vaseline and olive oil, etc., preferably glycerol, and / or The content of the lubricant is 1 to 15% by weight, preferably 3 to 5% by weight, based on the mixture.
6. The method according to any one of claims 3 to 5, wherein the foaming agent is selected from glucose, sodium bicarbonate and calcium hydroxide, preferably glucose, and / or The content of the foaming agent is 1 to 10% by weight, preferably 2 to 4% by weight, based on the mixture.
7. The preparation method according to any one of claims 3 to 6, wherein in step 1), the binder is selected from one or more of silica sol, alumina sol, starch, hydroxymethyl cellulose and polyvinyl alcohol, preferably one or more of silica sol, alumina sol and hydroxymethyl cellulose, and / or The content of the binder is 5 to 30% by weight, preferably 5 to 10% by weight, based on the mixture.
8. The preparation method according to any one of claims 3 to 7, wherein in step 1), the metal oxide is selected from one or more of ZnO, SnO, CuO, MnO2, ZrO2, CeO2 and CoO, preferably one or more of CuO, MnO2, ZrO2 and CeO2, and / or The content of the metal oxide is 1 to 20% by weight, preferably 5 to 10% by weight, based on the mixture.
9. A method according to any one of claims 3 to 8, wherein the water is deionized water, and / or The water content is 30 to 70% by weight, preferably 40 to 60% by weight, based on the mixture.
10. The preparation method according to any one of claims 3 to 9, wherein The kneading treatment time in step 1) is 0.5 to 24 hours, preferably 2 to 6 hours, and / or The number of times of repeating the mud kneading in step 2) is 2 to 15 times, preferably 5 to 10 times, and / or The aging time in step 3) is 1 to 48 hours, preferably 6 to 12 hours, and / or The extrusion pressure in step 4) is 0.5 to 20 MPa, preferably 2 to 5 MPa, and / or In step 5), the drying time at room temperature is 1 to 48 hours, preferably 12 to 24 hours; drying at elevated temperature refers to drying at 60 to 200° C., preferably 80 to 120° C., for 1 to 24 hours, preferably 2 to 6 hours, and / or. The calcination in step 6) refers to calcination at 400-800°C, preferably 500-600°C for 2-24 hours, more preferably 4-6 hours.
11. Use of the catalyst protective agent according to any one of claims 1 to 2 in waste gas treatment, such as tail gas treatment.
Citation Information
Patent Citations
Catalyst protective agent and preparation method thereof
CN101574669A
Methanol synthesis catalyst protection agent and preparation method thereof
CN110876935A
Sulfur-resistant shift catalyst protectant and its preparation method
CN112403484B
Sulfur-resistant shift catalyst protectant and its preparation method
CN114100695B
Catalyst for treating organic waste gas and preparation method thereof
CN101733127A